Getting Into the “weeds”: An Introduction to Common Lawn Plants and Their Ecological Benefits in North Central Florida - Olesya Malakhova; Wendy L. Wilber; Sandra B. Wilson; Kacey A. Russo; Jesse C. Jones; Brooke L. Moffis; Johanna Walker; Basil V. Iannone III (EDIS)
Maintaining monoculture lawns is resource intensive and can have environmental impacts on arthropod and aquatic communities. Here we introduce the reader to some of the many native plants that establish in lawns and if left to grow can provide ecological benefits to urban landscapes. Most resources and marketing regarding these plants focus on killing them rather than on their ecological benefits. This publication introduces the audience to these species and provides information about the biology and benefits of these species, as well as resources to learn more about self-recruiting lawn species.